2011
DOI: 10.1007/s11295-011-0413-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Moroccan grape accessions conserved ex situ compared to Maghreb and European gene pools

Abstract: Equipe DAVEM = Diversité et Adaptation de la Vigne et des Espèces Méditerranéennes Contact : ai.oualkadi@gmail.comGrape diversity present in Morocco and the part of this diversity used nowadays are poorly documented. In order to choose diversified genotypes, to select them so that their agronomic interest will be tested, a group of 21 autochthonous cultivars preserved in the germplasm collections of SODEA and 18 Moroccan cultivars from "Domaine de Vassal" INRA grape collection was compared to a group of cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
(29 reference statements)
3
7
0
Order By: Relevance
“…the number of alleles ranged from 6 (in UDV-015) to 12 (in VMc4c6 and VVS2) with a total of 90 alleles and an average of 9 alleles per locus ( Table 2), in agreement with previous analyses (7,14,31). out of 90 SSR amplicons, 83 were polymorphic with a high percentage of polymorphism (92.2%).…”
Section: Resultssupporting
confidence: 89%
“…the number of alleles ranged from 6 (in UDV-015) to 12 (in VMc4c6 and VVS2) with a total of 90 alleles and an average of 9 alleles per locus ( Table 2), in agreement with previous analyses (7,14,31). out of 90 SSR amplicons, 83 were polymorphic with a high percentage of polymorphism (92.2%).…”
Section: Resultssupporting
confidence: 89%
“…The values of these statistical parameters are typical for a species with high genetic variability, as reported in Laucou et al [9]. Regarding the Aglianico accessions analyzed in this work, the variety true-to-type [1,29] and the monophyletic origin of its biotypes (Taburno, Taurasi, and Vulture), suggested by Costantini et al [1], were confirmed. Aglianico biotypes are clonal lines selected in different growing areas noticeable for morphological and physiological traits.…”
Section: Discussionsupporting
confidence: 83%
“…The same three genotypes were confirmed after increasing the number of analyzed loci up to 43, during the second step of the work. The trueness-to-type for Aglianico and Sirica was attributed basing on the comparison of these results with the fingerprints reported in previous works [1,29]. The identity between Sirica accessions and Syrah [15] was checked and confirmed; just a discrepancy of 10 bp in the VMC2b5 locus was found.…”
Section: Identitysupporting
confidence: 65%
“…Grape (Vitis L.) is one of the most economically important fruit crops in the world (Reisch and Pratt 1996;Alleweldt 1997;El Oualkadi et al 2011;Myles et al 2011;Emanuelli et al 2013). The Vitis genus contains approximately 60 species widely distributed across three geographical regions: (1) South Europe and Asia Minor, (2) East Asia, and (3) North and Central America (Reisch and Pratt 1996;Alleweldt 1997;Wan et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Such interspecific crosses produce berries that are superior in quality in comparison to those in wild species that are directly cultivated (Reisch and Pratt 1996;Alleweldt 1997;El Oualkadi et al 2011).…”
Section: Introductionmentioning
confidence: 99%